ACCLIMATIZATION OF IN VITRO PROPAGATED RED BANANA (MUSA ACUMINATA) PLANTLETS - E. UZARIBARA; H. ANSAR; V. NACHEGOWDA; AMREEN TAJ; B. N. SATHYANARAYANA (The Bioscan, 2014)
The present study was carried out at Plant Tissue Culture Laboratory, Division of Horticulture, University of Agricultural Sciences, Gandhi Krishi Vignana Kendr, Bangalore during 2011-2012. Primary and secondary hardenings are integral and vital activities of the process of tissue culture banana. Propagation Studies on primary hardening media (cocopeat, vermicompost, sand and vermiculite) and secondary hardening mixtures [(red soil + sand + cocopeat (1:1:1 v/v), red soil + sand + FYM (1:1:1; v/v) and red soil + sand + vermicompost (1:1:1; v/ v)] of in vitro propagated Red bananan plantlets showed cocopeat was the best medium for primary hardening in terms of per centage survival of plantlets (95.00 %), plantlet height (5.58 cm), number of leaves (3.20), plantlet diameter (4.59 mm), number of primary roots per plantlet (5.20), length of primary roots (5.18 cm) and number of secondary roots per plantlet (25.50), whereas red soil + sand + cocopeat (1:1:1; v/v) recorded best results in terms of plantlet height (20.50 cm), plantlet diameter (11.60cm) length of leaves (15.43 cm), width of leaves (6.47 cm), number of primary roots per plantlet (12.30) and number of secondary roots per plantlet (331.20) followed by red soil + sand + FYM (1:1:1; v/v) mixture were good for secondary hardening. Finally concluded that combination of red soil + sand + cocopeat (1:1:1 v/v) was best medium for primary and secondary hardening of in vitro propagated Red bananan.